PENINGKATAN LITERASI MATEMATIKA SISWA SEKOLAH DASAR MELALUI PEMBELAJARAN KONTEKSTUAL - Fendrik, Muhammad (Jurnal Pendidikan Guru, 2017)
Mathematical literacy in the Programme for International Student Assessment (PISA) focuses on students ability to analyze, justify, and communicate ideas effectively, formulate, solve and interpret mathematical problems in a variety of forms and situations. Assessment is used to focus on problems in real life, regardless of the situation or problem that is often discussed in the classroom. Judging from the age of cognitive development, primary school students are still bound by concrete objects that can be captured by the five senses. In the abstract mathematics learning, students need learning tools such as media and props to further clarify what will be delivered by teachers so that they can more quickly understood and understood by students. Learning math is expected to give students an understanding of integrated, comprehensive and holistic about the material that has been presented. The understanding is not only meets the demands of substantive mathematics learning, but can provide significant benefits to students, this is in accordance with the purpose of contextual learning. Where contextual learning is an approach to learning that emphasizes the involvement of students in full process to be able to find the material studied and relate them to real life situations that encourage students to be able to apply it in their daily lives. There are four steps in implementing contextual learning, namely: motivation, comprehension, application, and assessment based on the components of contextual learning.